Analisis Campaign #FindYourShade dalam Inklusivitas Perempuan di Iklan Video Marketing Instagram @TirTir_Global - Tandaju, Christina; Azzahra, Wina Aulia; Koli, Nicodemus (Universitas Muhammadiyah Prof. DR. Hamka, 2025)
One of the main beauty standards for women shaped by media construction is that women must have fair, clean skin. TirTir, through the beauty campaign #FindYourShade, promotes cosmetic products to support skin tone diversity and emphasizes that all women are beautiful. The aim of this research is to examine how women are represented as part of the inclusivity message in the #FindYourShade TIRTIR marketing video. The research uses a qualitative semiotic method by Roland Barthes to analyze how media constructs inclusivity through the representation of diverse women, which can also be seen as part of the feminist movement. The research findings show that in the #FindYourShade marketing video on Instagram @tirtir_global, inclusivity messages about beauty for women from various backgrounds, races, ethnicities, and skin tones are represented.